Transformational Leadership, Knowledge Sharing, and Innovation Capability: Improving the Performance of MSME Organizations in East Nusa Tenggara Province - Johannes Anwar; Ferryal Abadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The competitive environment requires all organizations, including small, and medium enterprises (SMEs), to build competitive advantages to maintain and improve their performance. Transformational leadership and innovation capability are factors for organizations to improve competitiveness. This research aims to identify the influence of transformational leadership, knowledge sharing, and innovation capability on the performance of SMEs in the East Nusa Tenggara (NTT) Province. Research is using a quantitative method in the form of SEM-PLS. The data are collected using questionnaires distributed from April to July 2022 to 137 SME workers. The data are processed and analyzed using Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. The results show that transformational leadership positively affects innovation capability, knowledge sharing, and organizational performance of SMEs in NTT. The second finding concludes that knowledge-sharing activities can improve SMEs’ performance indirectly through mediating innovation capabilities. Finally, innovation capability encourages the improvement of SMEs’ performance in NTT. It also serves as a partial mediator of the influence of transformational leadership on organizational performance.